Implementasi Program “MEMASUNG” (Oral Motor Exercise, Massage, Susu Jagung) terhadap Kader Stunting Puskesmas Tirto, Kota Pekalongan: Implementation of the “MEMASUNG” Program (Oral Motor Exercise, Massage, Susu Jagung) for Stunting Cadres of the Tirto Health Center, Pekalongan City - Jihan, Jihan; Nooryana, Syavira; Amalia, Fitroh; Aulia, Mumtaz; Prafitri, Lia Dwi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
The stunting management program in the working area of the Tirto Health Center in Pekalongan City has not been comprehensive. The high incidence of stunting in Pekalongan, the limited training of cadres in stunting prevention and handling, and the lack of innovation in providing additional food for stunted toddlers are crucial problems identified. This service activity was carried out to accelerate the reduction in stunting rates by empowering 21 stunting cadres in the Tirto Health Center's work area in Pekalongan City. The activity lasted for four months and was carried out in three stages: partner socialization, implementation of activities, and monitoring, evaluation, and follow-up. The implementation of activities included education and early detection of stunting, oral-motor exercises and baby massage training, and demonstrations on making corn milk as an additional food for stunted toddlers. The results of the service activities for stunting cadres are an increase in cadre knowledge from 81% to 100%, cadres' skills in stunting early detection examinations from 14% to 100%, the ability to do oral motor exercises and baby massage from 0% to 100%, and the understanding of making corn milk from 0% to 100%. This community service activity demonstrates that the program implemented is effective in preventing and managing stunting in the Tirto Health Center's work area in Pekalongan City.